Introducing takaful in India: Prospects and challenges - Salman, Syed Ahmed (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2012)
The main objective of this research is to examine the viability of introducing takaful in India by investigating the prospects and challenges of introducing it. India is a multilinguistic country with the sacred feature of it is 'unity in diversity'. It is a country with 1.3 8 billion population and 13.6% of its population are Muslims. It has the third highest Muslim population after Indonesia and Pakistan. Thus, this study surveys the prospects and challenges of introducing takaful in India by questionnaire to the public and interviewing the insurance operators. Descriptive statistics is used to analyze the questionnaire and content analysis is used for interviews. The fmdings from the questionnaire show that the awareness of takafol is least but the acceptability of takafol and its expected prospects are very good. Moreover, the interview results show that insurance operators are able to offer the takafol products by extending product line or through Islamic windows although their staff need to go through training to be familiar with takafu/. In the opinion of insurance operators, the future of takaful is bright, provided that the government is willing to support it. Basically, it has been found that strengths and prospects of introducing takafu/ are more than weaknesses and threats. Thus, this study concludes that it is viable to introduce takafol in India.